Deontological manifestations of a lawyer’s legal awareness - Rudanetska, Oksana (Global Prosperity, 2023)
The article is devoted to the deontological manifestations of the lawyer’s legal consciousness. It is indicated that due to legal awareness, a person gets more opportunities to implement legal norms. At the same time, legal awareness promotes legal culture, participates in the formation of laws and the rule of law. In general, legal consciousness is defined as a process when people make sense of their experience based on legal categories and concepts. Among scientists, there is an expanded understanding of legal consciousness as a form of reflection of legal phenomena, which includes mental, intellectual, emotional and volitional processes and states. It is noted that deontological legal awareness is formed through the accumulation and functional interaction of many elements. The social functions of codes of professional ethics are indicated: they define ethical guidelines and best practices of the organization, which should be followed for honesty, integrity and professionalism; contain norms of a preventive and punitive nature, that is, violation of the code of ethics by members of a certain organization may lead to sanctions (in particular, dismissal). Codes contain principles formulated as statements of responsibility based on the understanding that the public good is always paramount; regulate business behavior within the profession and with other members of society; define professional value categories; promote compliance with professional and official discipline; contribute to the purification of the profession, thereby increasing the level of trustin legal professionals, legitimize jurisprudence and practical legal activity.